2013
DOI: 10.1007/s00726-013-1559-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ornithine decarboxylase activity promotes skin tumorigenesis by stimulating the recruitment of bulge stem cells but not via toxic polyamine catabolic metabolites

Abstract: Elevated expression of ornithine decarboxylase (ODC), the regulatory enzyme in polyamine biosynthesis, targeted to the epidermis is sufficient to promote skin tumor development following a single subthreshold dose of dimethylbenz(a)anthracene (DMBA). Since skin tumor promotion involves recruitment of hair follicle bulge stem cells harboring genetic lesions, we assessed the effect of increased epidermal ODC on recruitment of bulge stem cells in ODC-ER transgenic mice in which ODC activity is induced de novo in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This corroborates the fact that the minimal erythemal dose is higher than the minimal pigmentary dose in darker phototypes (Sklar et al, 2013). APC downregulated by 1 gene, known to regulate a diversity of biological processes, such as skin development, homeostasis, pigmentation, and disease including cancer (Lim and Nusse, 2013), was also modulated in the three populations, like ornithine decarboxylase 1, the first enzyme in polyamine synthesis, essential in normal growth, differentiation, and invasiveness of keratinocytes during tumorigenesis promotion (Hayes et al, 2014). The upregulation of the gene encoding matrix metalloproteinase 1 was confirmed in European and Indian subjects in agreement with previous data in lightly pigmented skin (Wang et al, 2014).…”
supporting
confidence: 77%
“…This corroborates the fact that the minimal erythemal dose is higher than the minimal pigmentary dose in darker phototypes (Sklar et al, 2013). APC downregulated by 1 gene, known to regulate a diversity of biological processes, such as skin development, homeostasis, pigmentation, and disease including cancer (Lim and Nusse, 2013), was also modulated in the three populations, like ornithine decarboxylase 1, the first enzyme in polyamine synthesis, essential in normal growth, differentiation, and invasiveness of keratinocytes during tumorigenesis promotion (Hayes et al, 2014). The upregulation of the gene encoding matrix metalloproteinase 1 was confirmed in European and Indian subjects in agreement with previous data in lightly pigmented skin (Wang et al, 2014).…”
supporting
confidence: 77%
“…Oncogenic mutations or mutational inactivation of tumor suppressor genes in the epidermal keratinocytes are known to drive the pathogenesis of skin cancers. A recent study using ODC-ER transgenic has shown that augmented epidermal ODC activity in the hair follicle bulge stem cells promotes skin chemical carcinogenesis [17]. …”
Section: Introductionmentioning
confidence: 99%
“…These promoters respectively target gene expression to inter-follicular epidermis and ORS of hair follicles [7, 17]. Chronic UVB-irradiation of these animals showed significant differences in the tumor phenotype, tumor numbers and tumor volume.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles of the issue are devoted to this enzyme. First evidence has been obtained that elevated levels of polyamines alone can stimulate the recruitment of epidermal bulge stem cells Hayes et al (2013). This is a significant finding with regard to the stem cell origin of skin cancer.…”
Section: Editorialmentioning
confidence: 98%